2005
DOI: 10.1073/pnas.0507551102
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional signaling pathway in the IFN system mediated by 2′-5′-oligoadenylate activation of RNase L

Abstract: Virus replication in higher vertebrates is restrained by IFNs that cause cells to transcribe genes encoding antiviral proteins, such as 2 -5 oligoadenylate synthetases. 2 -5 oligoadenylate synthetase is stimulated by dsRNA to produce 5 -phosphorylated, 2 -5 -linked oligoadenylates (2-5A), whose function is to activate RNase L. Although RNase L is required for a complete IFN antiviral response and mutations in the RNase L gene (RNASEL or HPC1) increase prostate cancer rates, it is unknown how 2-5A affects these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 41 publications
7
97
1
3
Order By: Relevance
“…2-5A-synthetases are activated by double stranded region of cellular RNA which leads to 2-5A synthesis [96,97]. But the identification of specific mRNAs regulated by RNase L was difficult to detect in intact cells until the advent of DNA microarray technology [98]. Activation of RNase L by exogenous 2-5A leads to general degradation (70%) of cellular RNA [99].…”
Section: ) Regulation Of Cellular Mrna Stabilitymentioning
confidence: 99%
“…2-5A-synthetases are activated by double stranded region of cellular RNA which leads to 2-5A synthesis [96,97]. But the identification of specific mRNAs regulated by RNase L was difficult to detect in intact cells until the advent of DNA microarray technology [98]. Activation of RNase L by exogenous 2-5A leads to general degradation (70%) of cellular RNA [99].…”
Section: ) Regulation Of Cellular Mrna Stabilitymentioning
confidence: 99%
“…We have recently shown that RNase L not only degrades RNA, it also induces at the transcriptional levels the expression of many genes [86]. For instance, the macrophage inhibitor cytokine-1 (MIC-1) gene is induced by RNase L in a pathway involving stress-activated kinases.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…In contrast, no 2-5A binding proteins were detected in several different organs of Rnasel −/− mice [69]. Therefore, the ability to bind 2-5A with high affinity (K D = 40 pM)[85] is a unique biochemical property of RNase L. As a result, 2-5A is an unambiguous signal for initiating RNA cleavage through activation of RNase L.We have recently shown that RNase L not only degrades RNA, it also induces at the transcriptional levels the expression of many genes [86]. For instance, the macrophage inhibitor cytokine-1 (MIC-1) gene is induced by RNase L in a pathway involving stress-activated kinases.…”
mentioning
confidence: 99%
“…2-5A mediated activation of RNase-L is predicted to primarily impact messenger RNA stability. However, a recent microarray analysis reported that 2-5A transfection resulted in the induction of more than twice as many genes as were repressed, suggesting that the biological activities of RNase-L are mediated by both RNA degradation and gene induction (Malathi et al, 2005). A comparison of gene expression in cells that exhibit senescent and apoptotic responses to 2-5A will provide a better understanding of the molecular basis of these outcomes.…”
Section: Activation Of Endogenous Rnase-l Induces Senescent and Apoptmentioning
confidence: 99%